Effects of garlic oil on milk fatty acid profile and lipogenesis‐related gene expression in mammary gland of dairy goats. (7th August 2012) - Zhu, Zhi; Hang, Suqin; Zhu, Honglong; Zhong, Sheng; Mao, Shengyong; Zhu, Weiyun
Abstract BACKGROUND: Garlic oil (GO) has blood lipid‐lowering effects. Milk fatty acid (FA) originates partly from plasma, and can be affected by the mammary lipogenesis. This study aimed to investigate GO effects on milk FA profile and mammary lipogenesis‐related gene expression. Early‐lactation goats were randomly allocated to four treatments with six goats each, and offered corn silage ad libitum and fixed amount of 0.79 kg day−1 dry matter (DM) concentrate mixed with GO (0, 0.57, 1.14, 1.71 g kg−1 DM) for 30 days consisting of 26‐day adaptation. RESULTS: Intake of corn silage reduced (P≤0.05) as GO level increased in the concentrate. Lipase activity and lactose content linearly increased, while non‐esterified FA concentration quadratically decreased with increasing GO level (P≤0.05). The proportions of short‐ and medium‐chain (C14:0, C15:0 and C16:0) and saturated FA decreased, whereas C18, cis9 trans11 conjugated linoleic acid (c9t11 CLA), t10c12 CLA, monounsaturated and polyunsaturated FA, and some ≥ C20 FA proportions increased in a linear manner with increasing GO level (P≤0.05). The mRNA abundance of genes remained unchanged (P > 0.1) as GO level increased. CONCLUSION: Garlic oil altered milk FA profile and these effects may not be related to the mammary lipogenesis‐related genes expression. © 2012 Society of Chemical Industry